TRIAL BALANCE APPLICATION IN THE SALON AYU BY USING MICROSOFT ACCESS 2000 - Jamilah Jamilah; Don Elsyafitra, Skom (Jurnal Sistem Informasi, 2002)
At the time of making reports of daily operations for the Salon Ayu done manually.In this way the error still occurs occasionally in making these statements and thedelay in submission of reports to the leadership, so that authors argue the need forapplications that can solve the problems encountered. By using Microsoft access willfacilitate the creation of reports and the code number estimates.